ESTIMATION OF RECTAL TEMPERATURE OF GOATS BASED ON SURFACE TEMPERATURE - Marques,Jordânio I. (2021)
ABSTRACT Infrared thermography (IR) is a non-invasive tool with potential to indicate changes in the animal’s thermal conditions in response to the thermally stressful environment. The objective of this study was to evaluate the application of IR to estimate the rectal temperature of crossbred goats of the Boer breed. Six male crossbred goats of the Boer breed were distributed in a completely randomized design and submitted to temperatures of 26, 30 and 34 °C. Rectal temperature (RT) and thermograms data were collected from animals at each air temperature evaluated. In the thermograms, the temperatures of the ocular globe (PT), head (HT), shoulder (ST), hindquarter (HQ) and maximum infrared (IRMax) of the animals’ surfaces were collected, the latter being observed in the lower region of the animals’ eyes, at all air temperatures evaluated. The correlation of PT, HT, ST, HQ and IRMax data with the RT was evaluated through the Pearson coefficient analysis and the concordance using Bland-Altman diagrams. With the exception of the IRMax surface temperature, the others were adequate for the accurate estimation of RT, with PT standing out for presenting the highest correlation coefficient with RT (r = 0.951) and estimation errors varying in the range of ± 0.27 °C.